THE EFFECT OF WORK DISCIPLINE AND HR CAREER DEVELOPMENT ON COMPANY PERFORMANCE AND ACHIEVEMENT - Adi Bandono; Okol Sri Suharyo; Sukmo Hadi Nugroho (Indonesian Naval Technology College STTAL, 2021)
Assessment of the performance and achievement of each unit of the company is very important to be carried out every certain period to provide a trigger for each unit in maintaining or improving the performance and achievements to be achieved. As for the better, the level of performance and achievement achieved by each unit will provide benefits to the company. Although currently there are sophisticated technologies that greatly impact various company activities and can improve the efficiency, performance, and achievement of human resources, it is an important factor in an organization. Human resources are very important to be given direction and guidance from human resource management to produce optimal performance. The optimal form of performance in human resources is influenced by the work discipline that exists in each employee/worker and the success of career development activities carried out by the existing human resource management at the company. This research was conducted to see how the influence of work discipline and career development in human resources on the performance and achievements of the company. Keywords: Work discipline, HR Career development, Company performance, and achievements.